EFFORTS TO ACCELERATE POVERTY REDUCTION THROUGH THE HUMAN DEVELOPMENT INDEX (HDI) IN THE SOCIETY - Suib, Moh. Syaiful; Hedi, Hedi; Muhaimin, Rizal (Nurul Jadid University, 2025)
Poverty is a scourge for local governments which has an impact on regional GDP. The government is trying to reduce it with various strategies. One of them is by optimizing HDI and increasing people's per capita income. The regional potential is very large for development, but it has not yet had a significant impact on the aspects of agriculture, plantations and tourism through regional UMKM. Why is it not optimal in several aspects to raise the HDI in Proboinggo Regency, especially in West Tiris? This research tries to explore strategies to reduce extreme poverty rates through the Human Development Index. The research method uses a descriptive analytical approach consisting of several stages used for variable exploration and strategy development. The results of this research are that people in West Tiris suffer from general obstacles including 1. education, namely limited access to schools, second: health, limited access to health services: Third, Economy and Income. Livelihoods in West Tiris are limited and still focus on less productive agriculture and plantations, some village youths have migrated out of the area.